Dysmenorrhea and Seborrheic Dermatitis due to Occupational Stress Among Female Bank Workers - Badri, Putri Rizki Amalia; Febriani, Ratika; Saraswati, Nia Ayu; Artanto, Ardi; Febrianti, Yuni; Apriyani, Selvy; Najwa, Annisya Nur (Universitas Airlangga, 2024)
Introduction: Bank workers who provide services to customers are required to have an optimal performance. They are vulnerable to stress that can interfere with their performance. Stress causes an increase in sebaceous glands, resulting in seborrheic dermatitis and an increase in hormones. This can cause contraction of the uterine muscles which can lead to dysmenorrhea. This study aims to determine the relationship between occupational stress and dysmenorrhea and seborrheic dermatitis among female bank workers. Methods: This research followed an analytic observational cross-sectional design using primary data from female workers at SumSel Babel Bank A. Rivai Branch. The sample consisted of 75 female bank workers, who met the inclusion and exclusion criteria and were selected using consecutive sampling. The independent variable in this study was occupational stress, while the dependent variables were dysmenorrhea and seborrheic dermatitis. Data were collected from primary data, the workplace stress scale questionnaire for occupational stress, the WaLIDD score for dysmenorrhea, and seborrheic dermatitis examination by a dermatologist. After obtaining the data, bivariate analysis was performed using the Chi-square test. Results: Sixty respondents (80%) had occupational stress, 47 respondents (62.7%) experienced dysmenorrhea, and 69 respondents (92%) did not experience seborrheic dermatitis. The results of statistical tests showed that there was a relationship between occupational stress and dysmenorrhea in female bank workers with a p-value 0.000 and no significant relationship between stress and the incidence of seborrheic dermatitis with p-value 0.202. Conclusion: Occupational stress can cause health problems including dysmenorrhea in female workers.